2015
DOI: 10.1017/s0960258515000318
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of QTLs for the micromorphology on the seed coat surface of soybean using recombinant inbred lines

Abstract: The seed coat of soybean (Glycine max (L.) Merrill) must protect the seed but allow water intake. Overprotection, causing impermeability, is assumed to be due to the presence of an impermeable layer in the seed coat, although validation of this assumption has relied on imbibition testing, which tends to be influenced by microfractures in the seed coat. Recent micromorphological analyses using laser-assisted topography microscopy revealed links to the surface roughness (SR) of the seed coat. To verify genetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In comparing our QTL results with QTLs for seed quality, we found that the qSV-C2.2 and qSV-C2.3 QTLs are new because they have not been associated with any other QTLs in previous reports. The qSG-A2 QTL was located close to QTLs for maturity (HAV4), seed viability (VIS4) (Watanabe et al 2004), and seed surface micromorphology (Otobe et al 2015). The mapped location of qSV-C2.1 was close to QTLs for germination rate (GRS1) and seed hardness (RAS1) (Watanabe et al 2004).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In comparing our QTL results with QTLs for seed quality, we found that the qSV-C2.2 and qSV-C2.3 QTLs are new because they have not been associated with any other QTLs in previous reports. The qSG-A2 QTL was located close to QTLs for maturity (HAV4), seed viability (VIS4) (Watanabe et al 2004), and seed surface micromorphology (Otobe et al 2015). The mapped location of qSV-C2.1 was close to QTLs for germination rate (GRS1) and seed hardness (RAS1) (Watanabe et al 2004).…”
Section: Discussionmentioning
confidence: 89%
“…The mapped location of qSV-C2.1 was close to QTLs for germination rate (GRS1) and seed hardness (RAS1) (Watanabe et al 2004). The qSV-D1b.1 QTL was located close to QTLs for seed hardness (RAS2) (Watanabe et al 2004) and a seed surface trait (qSR3) (Otobe et al 2015). For QTL associated with seed storability, Daragahi et al ( 2004) used the total of 128 SSR makers constructed 38 linkage groups and identified three QTLs on three linkage groups (C1, F and L) associated with seed storability in soybean under ambient condition (28 ± 2°C) for 5 months and accelerated aging (42 ± 1°C)…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The seed coat plays a protective role since cultivars with black or brown seed coats show better waterlogging tolerance than cultivars with a yellow seed coat (Hou and Thseng 1992;Rajendran et al 2019). Quantitative trait loci (QTL) mapping studies have shown a genetic link between seed coat pigments (Sayama et al 2009;Otobe et al 2015), surface roughness (Otobe et al 2015), and water impermeability. Yellow seed coat cultivars do not accumulate anthocyanins (anthocyanin glycosides) or proanthocyanidins (polymeric anthocyanins) (Todd and Vodkin 1993).…”
Section: Effects Of Waterlogging Stress During Germinationmentioning
confidence: 99%
“…There are several methods used for QTL mapping, including interval mapping (IM; Korol et al, 1995 ), composite IM (CIM; Utz and Melchinger, 1996 ), and multiple IM ( Kao et al, 1999 ). The QTL mapping methods have been used to examine the quantitative traits of many crops, including 100-kernel weight in maize ( Raihan et al, 2016 ), the carotenoids content in potato ( Campbell et al, 2014 ), the ratio of deep rooting in rice ( Horii et al, 2006 ; Lou et al, 2015 ), and the seed coat surface in soybean ( Otobe et al, 2015 ). The FPH is an important element of yield and has negative correlations with plant density and nitrogen rate in soybean breeding ( Mehmet, 2008 ).…”
Section: Introductionmentioning
confidence: 99%